Student Engagement and Academic Achievement in Adolescence: The Mediating Role of Psychosocial Development - de Carvalho Nuno Archer; Veiga Feliciano Henriques; Martínez Isabel; Veiga Carlota Margarida (Open Education Studies)
Academic achievement matters to students’ opportunities and well-being. Although previous research has shown the relation between achievement and student engagement, the role played by students’ developmental needs demands further deepening. In this context, the aim of the present study is to analyse the mediating role of psychosocial development in the relationship between student engagement and academic achievement. The study included 708 adolescent students between 11 and 19 years of age (M = 13.98, SD = 2.16) and used the Student Engagement in School Four-Dimensional Scale, the short version of the Erikson Psychosocial Stage Inventory, and the grades for Portuguese and Mathematics. Results showed significant, positive, and weak to moderate correlations between student engagement, psychosocial development, and achievement. Findings of structural equation modelling, controlling for gender, age, and school type showed that (1) industry fully mediated the relation between cognitive, affective, and behavioural engagement and achievement; (2) identity fully mediated the association between cognitive engagement and achievement, and partially mediated the relation between affective engagement and achievement. In conclusion, the findings highlighted the role of psychosocial development in explaining the relation between student engagement and academic achievement, thus opening new perspectives for research and action.